Analisis gaya bahasa pada puisi “nasihat ramadhan (buat mustofa bisri)” karya mustofa bisri: kajian stilistika - Nur, Muhammad (Maliki Interdisciplinary Journal, 2025)
This research aims to analyze the use of stylistics in the poem “Nasihat Ramadhan (For Mustofa Bisri)” by Mustofa Bisri. This poem is a literary work that is rich with religious and spiritual values, and uses various types of majas to strengthen its moral and spiritual messages. The method used in this research is stylistic analysis with a focus on identifying and explaining the use of majas such as rhetorical questions, metaphors, personification, antithesis, anadiplosis, epistrophe, parallelism, and repetition. The results of the analysis show that Mustofa Bisri succeeded in using these majas effectively to convey profound messages about self-introspection, self-control, and improving the quality of worship during Ramadan. Rhetorical questions are used to encourage readers to self-reflect, while metaphor and personification give a richer dimension to the spiritual meaning of Ramadan. Antithesis emphasizes the contrast between the physical and spiritual aspects of fasting, and anadiplosis and epistrophe stress the importance of doing everything for God. Parallelism and repetition reinforce the message of self-purification and control of every aspect of life. The poem “Nasihat Ramadhan (Buat Mustofa Bisri)” by Mustofa Bisri is a work that is not only aesthetically beautiful but also powerful in conveying a spiritual message. It inspires readers to live Ramadan with a deeper spiritual awareness, encouraging them to cleanse their hearts and souls of vices, and to draw closer to God with sincerity. As such, it serves as an important spiritual guide to the holy month of Ramadan.